1974
DOI: 10.1001/archneur.1974.00490370071011
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical and Genetic Studies in Two Families With Fabry Disease

Abstract: Genetic, biochemical, and enzymatic studies were performed in two families with Fabry disease. The urinary glycolipids and the leukocyte \g=a\-galactosidase, \g=b\-galactosidase,N-acetyl-\g=b\-glucosaminidase, and N-acetyl-\g=b\-galactosaminidase activities were determined in members of these families. Seven male members of both families had the typical symptoms of classic Fabry disease with abnormally low levels of \g=a\-galactosidase and increased urinary excretion of glycolipids.Female carriers who had mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1974
1974
1988
1988

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…Heat inactivation studies also showed low levels of a-galactosidase A, consistent with car rier status. We have not carried out hair root [6] or urine glycolipid [7] analyses to confirm the diagnosis. However, since the number of individuals with low activity was so high, there is also the possibility that some of them are low-activity variants and are not carriers of Fabry's disease.…”
Section: Discussionmentioning
confidence: 99%
“…Heat inactivation studies also showed low levels of a-galactosidase A, consistent with car rier status. We have not carried out hair root [6] or urine glycolipid [7] analyses to confirm the diagnosis. However, since the number of individuals with low activity was so high, there is also the possibility that some of them are low-activity variants and are not carriers of Fabry's disease.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it has been proposed that analysis of glycosphingolipids in the urinary sediment can be a usefuil adjunct in the diagnosis of a wide variety of glycosphingolipidoses including: Krabbe's leukodystrophy, Gaucher's, Fabry's, Sandhoff's diseases, and metachromatic leukodystrophy (5). Analysis of urinary sediment for trihexosylceramide and digalactosylceramide has been used to screen for hemizygotes and heterozygotes with Fabry's disease (5)(6)(7)(8)(9)(10)(11)(12) …”
Section: Introductionmentioning
confidence: 99%